Target experiences of workplace bullying: insights from Australia, India and Turkey. Issue 5 (1st August 2016) - D'Cruz, Premilla; Paull, Megan; Omari, Maryam; Guneri-Cangarli, Burcu
Abstract : Purpose: – The purpose of this paper is to explore target experiences of workplace bullying across Australia, India and Turkey, uncovering cross-cultural convergence and divergence. Design/methodology/approach: – A questionnaire-based qualitative data survey of business school students with current/prior work experience ( n =399) was undertaken. In total, 114 respondents (57 Australian, 34 Indian, 23 Turkish) identified themselves as targets of workplace bullying. Close-ended data pertaining to sociodemographic details were analysed via Statistical Package for the Social Sciences for descriptive statistics while open-ended data pertaining to experiences of bullying were thematically analysed against pre-figured categories derived from literature. Findings: – Manifestations of, etiology of and coping with workplace bullying were similar across all three countries, highlighting cultural universals. Clear variations in source of bullying behaviour and availability and use of formal interventions as well as more subtle variations relating to coexistence with category-based harassment, outcomes and bystander behaviour underscored the influence of national culture. Research limitations/implications: – Inclusion of a student population, notwithstanding their work experience, as well as reliance on the questionnaire as a tool pose limits in terms of external validity and communication congruence. Practical implications: – Understanding into the similarities and differences of workplace bullying across cultures facilitates the design of interventions tailor-made for a particular society, serving as inputs for international/multi-national and offshored business enterprises. Originality/value: – The study, focusing on multiple aspects of target experiences, not only draws on both dimensional and metaphorical cross-cultural frameworks but also includes geographically dispersed and socially diverse nations. Thus, it extends insights from previous cross-cultural explorations of workplace bullying which, apart from being few in number, are limited either by their frameworks, spatial range and/or thematic coverage.